Peran Segi Empat Kejahatan dalam Analisis Psikologi Forensik: Studi Kasus dan Implikasinya pada kasus Kasus kejahatan Pembunuhan 12 Orang oleh Dukun Pengganda Uang Banjarnegara - Amelia Indri Syaharani; Aisyah Shinta Balkhis; Ade Saputra; Gefira Adias Permata; Marshela Belina; Virza Ratna Diani (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to conduct a comprehensive analysis of the concept of the "crime quadrangle" from a forensic psychology perspective, focusing on the complex dynamics between the perpetrator, the victim, the criminal act itself, and the responses of society and the legal system. This concept describes crime as a phenomenon influenced by various factors, including the perpetrator's intent, the means used, the characteristics of the victim, and the circumstances that facilitate the commission of the crime. The focus of this research is on the murder case committed by "Mbah Slamet," a money-doubling shaman in Banjarnegara, highlighting how forensic psychology can help understand the processes and motives behind the crime. In this case, the suspect exploited the victims' trust through enticing promises of money multiplication, which ultimately led to the victims' deaths after they demanded the fulfillment of those promises. The suspect used psychological manipulation and trust deception techniques to influence the victims, who were willing to follow the rituals and ultimately were killed by poisoning. Through an in-depth psychological analysis of the chronology of these events, this research illustrates how the "crime quadrangle" can help identify important elements such as intent and psychological patterns underlying recurring crimes. These findings are expected to provide new insights for the field of forensic psychology in understanding and preventing similar incidents in the future, as well as supporting law enforcement efforts in handling cases involving manipulation and breach of trust.